Respectus Philologicus, 2009 Nr. 15 (20) - Bankauskaitė, Gabija (Respectus Philologicus, 2009)
CONTENTS I. PROBLEMS AND SOLUTIONS Joanna Korzeniewska-Berczyńska (Poland). The Communicational Aspect of Polish Political Discourse...11 Oleg N. Grinbaum (Russia). The Plot Heralds or Harmony and Metaphor in the Development of the Novel Evgenij Onegin by Pushkin...20 Virginija Jurėnienė (Lithuania). Lithuanian Women’s Aspirations for Presidency ... 34 II. FACTS AND REFLECTIONS Iosif Sternin (Russia). The Basic Types of Speech Cultures in Modern Society ...44 Hanna Mijas (Poland). A New Approach to Translating Culture in Subtitling ...53 Audronė Rimkutė (Lithuania). Cultural Industries and Cultural Policy: Traditional Relation and New Challenges ...62 Pavel Solovyov (Belarus). Language Picture of the World in Adjectival Figurative Comparisons ...76 Natalia V. Kovtun (Russia). Russia of the “Post Square” Epoch. (On the Issue of Poetics in the Novel Kish by T. Tolstoy) ...85 Izolda Gabrielė Geniušienė (Lithuania). Indeterminacy and the Search for Meaning in Geoffrey Hill’s Poetry ...99 Jerzy Szczepański (Poland). The Poet and the Period – Some Aspects of the Life and Work of Franciszek Karpiński (1741–1825) ...109 Natalia V. Yudina (Russia). On the Reflection of the Ethnic Stereotypes in the Mirror of the Russian Language ...121 Michał Łuczyński (Poland). Czech in the Pole’s Eyes – About the Reconstruction of the Stereotype ...134 Liudmila Arcimavičienė (Lithuania). ECONOMY Metaphors: What Associated Conceptions Underlie Lithuanian Business? ...143 Dorota Połowniak-Wawrzonek (Poland). Interpretation of THE METAPHOR PROCESSES RELATED TO HUMAN ORGANISM AS (ARMED) FIGHT, which Appears in Modern Polish Phraseology ...154 Daiva Aliūkaitė (Lithuania). Perceptual Analysis of the Dialectal Discourse: Mental Map ...164 Indrė Brokartaitė-Pladienė (Lithuania). Rendering German Coinages in the Newspaper „Naujasis Tilžės Keleivis“ (1924–1940) ... 180 Jūratė Čirūnaitė (Lithuania). Names of the Volyne Nobility in the 16th Century ...192 Danutė Balšaitytė (Lithuania). Vowel [ы] in Russian Speech of Lithuanians ...202 III. OPINION Olga V. Zernetskaja (Ukraine). Global Satellite News Networks: The Beginning of the 21st Century ...210 IV. OUR TRANSLATIONS Brigitte Peucker (USA). The Castrato’s Voice: Fassbinder’s In a Year of Thirteen Moons. Translated by Natalija Arlauskaitė ...220 V. SCIENTIFIC LIFE CHRONICLE Conferences, events Anatolij Kruglashov (Ukraine, Lithuania). Ukraine-Belarus-Poland-Lithuania: Recultivation of the Intellectual Space ...230 Viktorija Makarova (Lithuania). Patrick Seriot’s Lectures in Vilnius ...238 Books reviews Gabija Bankauskaitė-Sereikienė (Lithuania). Tekstai ir kontekstai: transformacijų sklaida. 1 volume. 2008...241 Saulutė Juzelėnienė, Daiva Aliūkaitė (Lithuania). Tekstai ir kontekstai: transformacijų sklaida. 2 volume. 2008...244 Oleg Perov (Lithuania). Lithuanian non Lithuanian – Evgenij Shkliar. ЛАВРИНЕЦ, Павел, 2008. Евгений Шкляр. Жизненный путь скитальца ...246 Skirmantė Biržietienė (Lithuania). BANKAUSKAITĖ-SEREIKIENĖ, Gabija, 2008. Oratorystės menas. Mokomoji knyga humanitarinių ir socialinių mokslų studentams ...250 Vilnius University Kaunas Faculty of Humanities: journal of scientific life Jūratė Svičiulienė (Lithuania). Cultural Industries: Challenges and Perspectives ...253 Daiva Aliūkaitė, Jadvyga Krūminienė (Lithuania). “Texts and Contexts: Interactive Perspectives“ or the Days of the Humanities at VU KHF ...255 Vytautė Pasvenskienė (Lithuania). TEXT Interface ...258 Daiva Aliūkaitė, Gabija Bankauskaitė-Sereikienė (Lithuania). Seminars on Literature and Linguistics at VU KHF ...261 Letters to the Editorial Board ...265 Announce...266 VI. REQUIREMENTS FOR PUBLICATION...268 VII. OUR AUTHORS...276